"Anger, embarrassment, less than a woman": the emotional impact of Black women's sexual pain. (2nd January 2023) - Malone, Natalie; Thorpe, Shemeka; Jester, Jasmine K.; Dogan, Jardin N.; Stevens-Watkins, Danelle; Hargons, Candice N.
ABSTRACT: Limited research has examined the emotions Black women report when thinking about sexual pain. To fill this gap in the literature, we explored the types of emotions that emerged when N = 126 premenopausal Black women thought about pain during sex. Open-ended responses to the following research question were analyzed: " What feelings emerge when you think about sexual pain? " Structural tabular thematic analysis was used to find commonalities in participants' responses. Findings indicated five families, or categories, of emotions: self-judgment, anger/disgust, sadness, anxiety, and emotions felt somatically. Additionally, women's reports were predominantly within the feeling state and cognitive appraisal components of emotion. Implications for health providers and therapists are discussed.